The favorability of orographic and edaphic factors for the main species that comprise urban forests from Brasov City - Raluca ENESCU; Diana VASILE; Lucian DINCĂ; Șerban DAVIDESCU; Iuliana Gabriela BREABĂN (Present Environment and Sustainable Development, 2022)
Urban forests, which means all trees, shrubs, lawns, and other vegetation from cities are very important spaces that are protected in order to protect and conserve biodiversity and the region’s structure. These forests have economic, social, and ecological functions. The research was realized in urban forests from Brasov city. The favorability of certain orographic and edaphic factors were determined for the selected species (by using these property values and sheets regarding the species ecological requirements (Norway spruce, silver fir, beech and sycamore). If we consider the ecological requirements of the main species that comprise the studied stands and a series of orographic (altitude) and edaphic factors (reaction, base saturation degree, edaphic volume, potential global trophicity), we were able to calculated the favorability of species based on grades. The conclusion was that Norway spruce has the highest favorability, followed by common beech. Even though silver fir has a lower favorability then Norway spruce, all plots have fir and Norway spruce in their composition. Furthermore, it can be observed that a higher favorability, as in the case of sycamore, does not necessarily determine its presence in more areas. On the contrary, sycamore appears only in a very low number of plots.